Genre-Based Approach: Can It Improve the Informatics Engineering Students’ Writing Skill? - Sukmawati, Nur Najibah; Nasution, Sukma Septian (JEES (Journal of English Educators Society), 2020)
Because instructional process in English for Specific Purpose (ESP) context is oriented to students’ academic and professional settings within discourse community, challenges appear. Learning language and learning language are directed to improving students’ language skills to survive the 21st century. On the other hand, score-documentations proved that the students performed low skills; especially writing skill. This study aimed at improving the students’ skill in writing explanation text by using Genre-Based Approach (GBA) to Informatics Engineering students of a private university in South, Indonesia. Classroom Action Research (CAR) was conducted to the third semester students of the university within two cycles. To validate the findings, writing test, observation and questionnaire were employed. The test result proved implementing GBA improved the classroom’s average score from 54 to 59.95 in cycle 1. This improvement was supported by the students’ engagement and enthusiasm to the instructional process as suggested by questionnaire and observation respectively. Further, the implementation of cycle 2 revealed the average score improved from 59.5 to 70.5. This score improvement is followed by the students’ agility and cooperativeness during the instructional process. This concludes that implementing GBA can improve the students’ skill in writing explanation text. This finding is expected to give insight for teachers to undoubtedly using GBA in English for specific purposes context. HIGHLIGHTS: The instructional practice of teaching English for informatics engineering students in the private university still focuses on form-based mastery. The informatics engineering students are eager and high-determinate to learn language skills especially writing in collaborative framework.